Durations required to distinguish noise and tone: effects of noise bandwidth and frequency - Taghipour, Armin; Moore, Brian C. J.; Edler, Bernd (Journal of the Acoustical Society of America, 2016)
Perceptual audio coders exploit the masking properties of the human auditory system to reduce the bit rate in audio recording and transmission systems; it is intended that the quantization noise is just masked by the audio signal. The effectiveness of the audio signal as a masker depends on whether it is tone-like or noise-like. The determination of this, both physically and perceptually, depends on the duration of the stimuli. To gather information that might improve the efficiency of perceptual coders, the duration required to distinguish between a narrowband noise and a tone was measured as a function of center frequency and noise bandwidth. In experiment 1, duration thresholds were measured for isolated noise and tone bursts. In experiment 2, duration thresholds were measured for tone and noise segments embedded within longer tone pulses.<br